Campus e cidade: uma análise dos impactos do UNIPAM no espaço urbano de Patos de Minas-MG - Rodrigues, Renata Aparecida Vaz (2016)
This research analyses the urban impacts and transformations created by UNIPAM’s university campus implanted in the seventies at the average city of Patos de Minas in Minas Gerais. The university campus is considered an strategic urban component to develop the productive potential of an average city. The main objective intend to analyze the university’s influence in the urban form around campus. For that, was defined ten categories to analyze one of the areas of direct influence of UNIPAM campus. The categories of analyzes systematize the data collected and focus on: spacial syntax, buildings construction periods, occupancy rate, template, buildings function, relationship between the campus and the city, legislation, HDI- Municipal Human Development Index, land value and urban mesh. The discussion of the categories validated the preposition about the campus being considered a transformation agent witch impacts the urban space, with the potential of altering its uses, the constructive typology, a occupation density, the mesh of edifications among others.